ANALISIS PERSEPSI PERAWAT TERHADAP BUDAYA KESELAMATAN PASIEN DENGAN PENDEKATAN INSTITUTE FOR HEALTHCARE IMPROVEMENT DI RSJD DR. AMINO GONDOHUTOMO KOTA SEMARANG - Asri Pratiwi; Sudiro Sudiro; Eka Yunila Fatmasari (Jurnal Kesehatan Masyarakat (Undip), 2017)
The Lack of nurses perception on patient safety culture could be one of the causes of about 60 incidents in a year in RSJD Dr. Amino Gondohutomo. Nurses have an important role in communication, where communication becomes important in patient safety. The aim is to determine nurses perception on patient safety culture with Institute for Healthcare Improvement approach in RSJD Dr. Amino Gondohutomo Semarang. Method used was qualitative descriptive by using interview guidelines as instrument, The primary Informant are 5 nurses in UPIP. Result, the nurse perception that involved patient in safety initiation is deficient, because it is done when the patient, in to get information related to patient’s history.Relay patient safety report in shift changes is already done with procedurs. Conduct safety briefing is deficient because it is only done as the evaluation when the incident occurred, not as a precaution. Open culture, just culture, reporting culture, learning culture, and informed culture have been created although few things need to be done to improve the safety culture. Suggestions do family gathering regularly, conduct patient safety briefing, inform incident reporting procedues, and for nurses more open in discussion of patient safety.